Numerical Simulation of Two-Phase System of “Combustible Liquid – Solid Fuel” Combustion in a Fixed Bed - K. V. Dobrego; I. A. Koznacheev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2019)
Investigation of combustion of complex heterogeneous systems and particularly of twophase “combustible liquid – solid fuel” systems is topical because of the need to improve combustion of multicomponent and non-standard fuels as well as for resolution of specific ecological problems. The qualitative and quantitative peculiarities of combustion of two model combustible systems, notionally corresponding to the “sawdust – oil” and “wood chips – oil” mixtures are investigated numerically. The main peculiarity of the systems is volatility of the fluid component, being gaseous-flow driven inside porous media. A one-dimensional plain problem of combustion of compact layer with the ignition from the bottom and from the upper side is considered. It is demonstrated that due to low gas permeability of the fine-dispersed solid matrix (sawdust), air flow velocity is relatively low which results in slow formation of the combustion front (the characteristic time is tens of minutes). In case of coarse solid phase (wood chips), airflow rate is higher and corresponding time of temperature fronts formation is smaller (a few minutes). Both for the cases of fine-dispersed and coarse particles solid matrix phase, when set on fire from below, the fluid component is evacuated from the hot zone before the combustion front is formed. Since that, the main characteristics of the temperature front dynamics correspond to “dry” fuel system. In case of upper side ignition the combustion wave is formed at the time of the order of 100 s (when the used magnitudes of parameters are being used again), then it spreads downstream of the layer, accompanied by incomplete oxidation of solid fuel and complete combustion of oxygen. The effect of incomplete solid fuel combustion was noted earlier in the investigations of combustion of lean coal layer and some other systems. The velocity of the combustion wave propagation does not differ much for the cases of upper side and bottom side ignition. But the time of establishing the quasi-stationary velocity of the front to the steady-state value at the initial stage is much less in case of bottom side ignition. The results obtained by the authors can be utilized for optimization of multi-phase fuels combustion in compact layer, the regime parameters of in-situ combustion method of oil recovery increase as well as for improvement of some specific chemical processes.